The effect of Disney animated films (Cinderella, Sleeping Beauty and Mulan) to the gender-role perception of children - Aficial, Maricris G.; Calimquim, Maricar S.; Esita, Jemellee Y. (2003)
Mass media has been affecting the new generation of children in perceiving their gender-roles. The repetitive gender-role portrayals- that are most of the time stereotyped, selective and exaggerated-in Disney animated films does not reflect what really a girl and a boy should be. Disney animations formed a culture in gender-roles ever since it started. Most depictions of girls are usually beautiful,obedient, patient, meek and fragile. On the other hand, boys are masculine, heroic and strong. These gender-role stereotypes leave a powerful message that girl is the weaker sex and boy is the stronger sex. A content analysis of three selected Disney animations revealed that these films contained many gender-role stereotypes that are affecting the gender-role perceptions of children who are avid viewers. The film showing and interviews to the grade-one student of Saint Louis Laboratory Elementary School showed that their gender-role perception are also stereotyped. The theme and characterization of the films are the main contributors in such stereotyped perceptions of these children. It was also found out that the culture passed to them by their parents is also a factor why they agree on all the gender-role depicted on these films. It was also revealed that the introduction of a less-stereotyped animation Mulan is not that effective to change their perceptions about gender-roles. More films like that of Mulan should be introduced in able to meet gender transcendence. In this regard, a more critical evaluation of Disney animations content is needed. It is important that stereotypical content of these films should be minimized or better, be change -- Author's abstract.
Thesis (B.A.) -- University of the Philippines Baguio, 2003.
Includes bibliographical references.
Keywords: Disney characters -- Psychological aspects; Animated films and children